Approaching risk management: An overview on critical success factors and challenges - Flora Bernardel; Roberto Panizzolo (The International Journal of Management Science and Information Technology (IJMSIT), 2012)
Business organizations have recently experimented an increasing risk exposure due to several exogenous factors (e.g. the legal and regulatory framework, the technological innovation and the volatility of financial markets and commodities), actually exacerbated by the current economic crisis affecting all sectors and companies. In addition, the new risk configurations refer more closely to networks or supply chains, in which individual organizations operate in order to achieve their business objectives. Thus, in a supply chain context, a structured, effective and efficient risk management process becomes a fundamental tool for organizations and their governing bodies in particular, in order to develop economic balances, to support long-term value creation and to protect the entrepreneurial assets. This paper provides some useful insights on critical success factors and challenges encountered by organizations approaching risk management initiatives. The discussion is centered about network risk, in order to emphasize the negative potential of criticalities and threats arising from the competitive environment. Starting from the interpretive review proposed, through the analysis of the main risk-facing strategies, it will be clear how companies are trying to overcome the traditional model focused on the primary activities of the value chain and supply chain processes, in order to adopt a risk management approach.
Keywords: 650; Organizational Risk; Network Risk; Supply Chain Risk Management; Risk Management Strategies; Operations Risk; Risk Challenges